ROLE OF ENDOSCOPIC THIRD VENTRICULOSTOMY VERSUSVENTRICULOPERITONEAL SHUNT FOR RESOLUTION OF PAPILOEDEMA INPATIENTS OF PAPILOEDEMA ASSOCIATED WITH HYDROCEPHALUS (Journal of Medical & Health Sciences Review, 2025)
Objective: To compare the efficacy of Endoscopic Third Ventriculostomy (ETV) versus Ventriculoperitoneal Shunting (VPS) in resolving papilledema in patients with obstructive hydrocephalus.Methods: A non-randomized controlled trial was conducted at the Department of Neurosurgery Unit III, Punjab Institute of Neurosciences, Lahore, from January 2023 to December 2023. Forty-four (44) patients with hydrocephalus and associated papilledema were included. Participants underwent either VPS or ETV. The primary outcome, resolution of papilledema, was assessed using the Modified Frisén grading scale at 2 weeks and 6 weeks postoperatively. Statistical analysis was performed using the sample t-test, with a significance level set at p < 0.05.Results: Both VPS and ETV procedures resulted in a statistically significant reduction in papilledema severity as measured by Frisén grading (p < 0.05 for each procedure). However, there was no statistically significant difference in the degree of papilledema reduction between the VPS group and the ETV group at either the 2-week or 6-week follow-up intervals.Conclusion: Both Ventriculoperitoneal Shunt (VPS) and Endoscopic Third Ventriculostomy (ETV) are effective surgical interventions for reducing papilledema in patients with obstructive hydrocephalus. The findings suggest equivalent efficacy between the two procedures specifically regarding papilledema resolution. The choice of procedure can therefore be based on other patient-specific factors, surgical risks, and clinical considerations.